CMTM86 The new standard (ISO 14649) to address process planning and machining - Yusof, Yusri (2010)

(untitled)
Literatures show that the current CNC is difficult to manage, modify and verify NC data easily. ISO 14649 referred to as STEP-NC is the result of an international effort to achieve full interoperability and bidirectional information exchange throughout the manufacturing network. STEP-NC has been designed in such a way that information remains in its context and without reducing to primitive instructions such as G&M code. This research will explore ISO 6983 (G&M Code) together with ISO 14649 (STEP-NC) and utilize STEP-NC in overcoming the problems of G&M code at the same time take advantage of current advances in computing and controllers. A new STEP NC Code Generator which focuses on the milling process that are able to generate STEP-NC codes based on Example 1 in ISO 14649 Part 12 will be developed. The advantages of the proposed Code Generator program will be verified and evaluated. The Code Generator can understand and generates STEP-NC codes through a STEP-NC compliant interface and will give industries and academician more in-depth of understanding and confidence to switch from G&M code to STEP-NC.